FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA KELUHAN MSDs PADA PEKERJA PERKANTORAN DI PT. Y TAHUN 2024 - Syam, Andi Kesya Balqis; Iriani, Dewi Utami (Public Health Study Program, Faculty of Health Science, State Islamic University (UIN) Syarif Hidayatullah Jakarta, Indonesia., 2025)
Offices are workplaces that have various potential dangers for workers, one of which is Musculoskeletal Disorders (MSDs), which are complaints of tendons, nerves and joints ranging from mild complaints to very painful ones. MSDs usually occur due to individual factors, work factors, and environmental factor This study aims to determinethe factors associated with MSDs complaints among office workers at PT. Y This research is quantitative with a cross-sectional design and the number of respondents was 54 people. In this study, it was found that 34 workers experienced moderate levels of MSDs. There was no relationship between age (P-value=1.000), gender (P-value=0.552), physical activity (P-value =0.877), years of service (P-value=0.889), BMI (Pvalue =0.197), smoking habits (P-value =0.127), work posture (P-value=0.223) with MSDs complaints. The majority of workers (98.1%) have risky work postures due to inadequate work stations and low physical activity (42.6%). PT. Y is advised to provideappropriate work stations for its workers, and needs to create a physical activity program to increase the physical activity of office workers. Workers are advised to pay attention to body posture when working and do regular physical activity. Keywords: MSDs, Office Workers, ROSA